Historic structure and cultural consciousness: The space regeneration of Jinling Machinery Manufacturing Bureau, China - Xiong Xiangrui; Wang Yanhui; Sabaté-Bel Joaquín (Lodz University of Technology Press, 2023)
Different forms of historic structures within the city show diverse cultural and social factors that not only shape the urban personality, but also construct the complexity of historical and modern spaces. Therefore, as far as urban renewal is concerned, on the one hand, it is essential to protect historic structures to stimulate cultural consciousness of spatial intervention in order to preserve the urban personality and on the other hand, it is necessary to reuse historic structures to keep the possibilities of a continuous dialogue between the past, the present and the future of the city. Through the methods of historical analysis and empirical research, this paper takes the renewal of Jinling Machinery Manufacturing Bureau (JMMB), the modern industrial site, as a case to analyze the relationship between historic structures, cultural consciousness and urban development on two scales -urban areas and plot. The research shows that: 1) the continuation of a stable historic structure is the key to maintain cultural identity in the process of space regeneration; 2) the historic structure contains tangible space forms and historical narrative logic; 3) the cultural consciousness determines the value orientation of space regeneration; and 4) the new functions match culture themes that can promote social values of space regeneration.
Keywords: urban renewal; urban form; historic structure; cultural consciousness; industrial heritage; rewitalizacja miast; forma urbanistyczna; struktura historyczna; świadomość kulturowa; dziedzictwo przemysłowe